The Impact of Abdominal Obesity Status on Cardiovascular Response to the Mediterranean Diet - Alexandra Bédard; Sylvie Dodin; Louise Corneau; Simone Lemieux (Hindawi Limited, 2012)
We investigated the impact of abdominal obesity status on the cardiovascular response to a fully controlled 4-week isoenergetic Mediterranean diet (MedDiet). Thirty-eight abdominally obese individuals (waist circumference >102 cm in men and >88 cm in women) and thirty-one nonabdominally obese individuals were recruited and studied before and after the MedDiet. All analyses were adjusted for the slight decrease in body weight, which occurred during the MedDiet (mean: 0.9±1.2 kg). A group by time interaction was noted for waist circumference (P=0.02), abdominally obese subjects showing a significant decrease and nonabdominally obese subjects a nonsignificant increase (resp., −1.1 and +0.3%). The MedDiet resulted in decreases in total cholesterol, LDL-C, HDL-C, apolipoprotein B, A-1, and A-2, total cholesterol/HDL-C ratio, LDL-C/HDL-C ratio, and systolic and diastolic blood pressure (time effect: P<0.05). For all variables related to glucose/insulin homeostasis, no change was observed except for a decrease in 2 h glucose concentrations (time effect: P=0.03). No group by time interaction was observed in any of the metabolic variables studied. Results from our study suggest that the adoption of the MedDiet leads to beneficial metabolic effects, irrespective of the abdominal obesity status.